Feasibility of using calibrated cone-beam computed tomography scans to validate the heart dose in left breast post-mastectomy radiotherapy. Issue 6 (June 2020) - Tang, Bin; Ma, Jiabao; Xu, Jinghui; Li, Jie; Kang, Shengwei; Wang, Pei; Wu, Fan; Orlandini, Lucia Clara
Objective: In post-mastectomy radiotherapy, high-conformal techniques are a valid method for determining the dose distribution around a target. However, the proximity of critical structures is a reason for concern. This study aims to evaluate the feasibility of using calibrated cone-beam computed tomography (CBCT) scans as a valid tool for a timely heart dose evaluation. Methods: A retrospective analysis was conducted on 170 retrospective CBCT scans of 17 patients who underwent high-conformal post-mastectomy irradiation. The delivered doses that were calculated using personalized calibrated CBCT were compared with the doses planned, using the dose–volume histogram dosimetric parameters. Results: The heart volume that was evaluated using CBCT presented a mean increase of 6%; this discrepancy impacted the heart dose in 4 of 17 patients, with an absolute increase of V25 Gy (range, 2.5%–7.6%) and an increase in the mean dose (range, 1.1–3.4 Gy). The dose for the target, ipsilateral lung, and contralateral breast remained unchanged. Conclusion: Using CBCT to monitor the dose that is delivered to the heart is feasible, allowing for a timely shift to an adaptive plan if clinically necessary.